2007
DOI: 10.1093/aob/mcm155
|View full text |Cite
|
Sign up to set email alerts
|

Genome Dissection of Traits Related to Domestication in Azuki Bean (Vigna angularis) and Comparison with other Warm-season Legumes

Abstract: BackgroundThe objective of this study was to dissect into quantitative trait loci (QTLs) the large morphological and physiological differences between cultivated azuki bean (Vigna angularis) and a wild relative and to infer the commonalities of the QTLs for domestication-related traits across the Asian Vigna and with other warm-season legumes.MethodsTwo linkage maps, for the BC1F1 and F2 populations, respectively, from the same cross between azuki bean and V. nepalensis were developed. Using these linkage maps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 38 publications
7
111
0
2
Order By: Relevance
“…Some factors other than pod morphology could be associated with pod dehiscence, such as a cell wall-degrading enzyme (Christiansen et al, 2002) and twist strength of pod wall (Isemura et al, 2007), which is presumed to be a force to dehisce pods. Very recently, the chemical composition of the pod wall in cultivars susceptible to shattering was found to differ from that in the shattering-resistant cultivars (Romkaew et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some factors other than pod morphology could be associated with pod dehiscence, such as a cell wall-degrading enzyme (Christiansen et al, 2002) and twist strength of pod wall (Isemura et al, 2007), which is presumed to be a force to dehisce pods. Very recently, the chemical composition of the pod wall in cultivars susceptible to shattering was found to differ from that in the shattering-resistant cultivars (Romkaew et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis of pod shattering has been carried out in various legumes including soybean [48,[93][94][95][96][97][98][99][100][101], common bean [13,44], pea [18,50,102], cowpea [49,[103][104][105][106], lentil [16,46,107], narrow-leaf lupin [47,108], azuki bean [45,109], and common vetch [43,110]. In most of the legumes that have been studied so far, pod shattering is found to be a dominant trait controlled by one or two genes or QTLs (Table 1).…”
Section: C Shattering In Legumesmentioning
confidence: 99%
“…In common vetch, Vicia sativa, shattering was found to be controlled by a single gene, and recessive mutants were selected during domestication for their non-shattering character [43]. Similar to common vetch, a single gene controls the shattering process in azuki bean, Vigna angularis [45,109]. In narrow-leafed lupin (Lupinus angustifolius), two genes are involved in controlling the recessive non- shattering trait [108].…”
Section: C Shattering In Legumesmentioning
confidence: 99%
“…The QTLs for the domestication related traits in azuki bean were identified in three populations derived from two cross combinations 7,10 . In this review, the QTL regions that were identified in the BC 1 F 1 population 7 were compared with those in rice bean, since the QTL regions were identified in the BC 1 F 1 population in rice bean 8 . Almost all common molecular markers showed a high level of co-linearity within the same linkage group.…”
Section: Comparison Of Qtl Regions Associated With Domestication Betwmentioning
confidence: 99%
“…For 28 traits, a total of 76 QTLs were found in azuki bean 7 , whereas 69 QTLs were found in rice bean 8 . In azuki bean, the QTLs with large effect (PEV > 20%) were found on five linkage groups (LG1: seed dormancy and internode length, LG2: seed size and epicotyl and lower internode length, LG7: pod dehiscence and pod size, LG8: pod size, and LG9: twining habit) (Fig.…”
Section: Difference In Number Of Qtls and Linkage Groups Associated Wmentioning
confidence: 99%